Digital competences in the elderly and university students: didactic interaction from the use of social networks - Holguin Alvarez, Jhon Alexander (2021)
Digital Competences mediate the population of vulnerable Latin American contexts. In these there is the need to expand social communication as a way of learning and self-improvement. This research proposes to determine the effects of transfer of digital competences in two types of interaction: university students-adults, adults-schoolchildren. Therefore, two groups of individuals participate in two experimental phases of didactic transfer through the use of social networks, based on the execution of a Research Seed Project and another Project of Professional Practices of Social Responsibility in vulnerable contexts. We found effectiveness in the transfer of Digital Competences in both cases during more than six months of project execution. We report greater predisposition for the acquisition of information, communication, self-evaluation and access to information in adults. The schoolchildren managed to reinforce their skills to apply Digital Safety and Problem Solving, improving notably in this group. This program is seen as part of the improvement of teaching that every school needs as a means of curricular strengthening, whether they are teachers of advanced age or students of the primary stage. We believe that these skills will open up to the professional world with better visionary prospects for developing countries.